NEGARA VIS A VIS CIVIL SOCIETY MASA TRANSISI: Studi Counter Hegemony Himpunan Mahasiswa Islam Majelis Penyelamat Organisasi (HMI MPO) terhadap Rezim Habibie - Subhan Agung (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
Target of this research are : first, to know the perception of HMI MPO to Habibie transition regime in its relation with people. Second, to know strategy and movement manifestation of HMI MPO in conducting counter hegemony to Habibie transition regime. This Research uses descriptive qualitative method. Informan technique intake use purposive sampling. Process selection use snowball sampling. Where all informan are collegiate, cadre which have been involved active, and outsider HMI which the history eyewitness personating Analysis methods use interaktif analysis method, and also the validity data with triangulation data. The Perception of HMI MPO to Habibie transition regime in its relation with people is that Habibie regime is regime which nonalignment at people (dhalim), hegemonic like Soeharto regime and have to be fought against. Hegemonization Habibie regime toward people strength element conducted by: policy intake process which do not populis, represif and militeristic, existence of society strength element polarization effort, its low respect to women political aspiration and existence of leting to uncertainty law to the a number of big case, especially the heavy HAM collition in Trisakti and Semanggi case.